Psychological and Pedagogical Support of the Future Social Work Specialist’s Professional Development - Khvorikova, E.G. (2022)
The article focuses on the issue of psychological and pedagogical support in the professional growth of a social worker. The main structural components of the professional and personal development cover the cognitive, motivation-axiological, social-perceptive, emotional-volitional and communicative spheres of the human activity. The future social work specialist’s competency development is a result of a continuous internal struggle for the spiritual perfection, realization of the creative potential, achievement of wholeness, and the determination to abandon the “thing-in-oneself”-state in behalf of the “better-self”-development. The essential premise for the professional development of a social worker is the possibility to choose ways of professional self-realization in the ambiguity zone and the necessity of the certainty zone existence. These two zones allow the future specialists to actualize their motivation of choosing the ways to their professional development. This actualization goes more efficiently if there is interaction of the parties united by the shared goal and activity, which develops different forms of collaboration and discloses individual creative features. It has been established that the psychological and pedagogical model of the future social work specialist’s development includes the following core constituents: the study and development of the professionalism structure and its components on the basis of its development indicators; the consideration of psychological and pedagogical conditions and factors ensuring productive development of the social sphere specialists; the formation of the need in self-realization, the development of communicative skills, creative and individual potentials, teaching self-regulation and self-perfection skills. The model creates premises for the effective realization of the continuity principle as it characterizes the nature of the ‘actual development zone’ and focuses on the “proximal development zone”